Sistem Pembacaan Kode Pos yang Terintegrasi dengan Pencarian Alamat pada OpenStreetMap - Adrian Evan; Leo Willyanto Santoso; Rudy Adipranata (Jurnal Infra, 2020)
Postal code consist of sequential data which refers to a certain address in detail to their smallest form such as rural areas that are seperated by its own respective digits except the tiniest rurals. On the contrary, these pieces of data cannot be used conveniently on map database due to its thorough categorization and filtering process. Some of them may uncorrelated and may cause misunderstanding as of commonly existing digital maps merely processing longitude, latitude, also address data to city level simply using plain text.To solve the database system and postal data system disjoint problem, these two separate yet potentially powerful systems has to be integrated. With the continuous web development and securer HTTPS protocol into practice, also putting Progressive Web Apps into consideration, these core address finding functionsnamely geocoding, geolocation, also reverse geocoding majorly functions optimally without any need to concern users’ convenience on using this merged system at any sort.Test results conclude that this merged system has been significantly improving location finding accuracy, as long as the system works within the right hands. Basic knowledges of mapping system and GIS are inevitably mandatory to unleash existing maps capability of location finding into deeper levels. This will operates even optimally when the postal data system are wholefully implemented into the querying process, in addition to another smart features, such as shortest/fastest route tracking also traffic/riot detection into play.